2020
DOI: 10.1177/0300060519879293
|View full text |Cite
|
Sign up to set email alerts
|

Rare missense variant p.Ala505Ser in the ZAK protein observed in a patient with split-hand/foot malformation from a non-consanguineous pedigree

Abstract: Objective: Split-hand/foot malformation (SHFM) is a rare, often debilitating, congenital limb malformation. A single nucleotide polymorphism within the leucine zipper containing kinase AZK (ZAK) gene was recently associated with SHFM in two consanguineous Pakistani pedigrees. We hypothesized that additional unrelated patients with the phenotype may carry a pathogenic mutation in ZAK. Methods: DNA samples were collected from 38 patients with SHFM and associated hearing loss for Sanger DNA sequencing and in sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Spielmann et al 26 have found that Map3k20 , a gene within the deletion region, is expressed in developing limbs. Furthermore, the authors summarized the clinical manifestations of Map3k20 mutations, including split‐foot malformation with mesoaxial polydactyly, which is related to hearing loss and exhibits a possible clinical phenotype of cutaneous syndactyly 26,27 . Herein, cutaneous syndactyly was an important malformation in the examined fetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spielmann et al 26 have found that Map3k20 , a gene within the deletion region, is expressed in developing limbs. Furthermore, the authors summarized the clinical manifestations of Map3k20 mutations, including split‐foot malformation with mesoaxial polydactyly, which is related to hearing loss and exhibits a possible clinical phenotype of cutaneous syndactyly 26,27 . Herein, cutaneous syndactyly was an important malformation in the examined fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the authors summarized the clinical manifestations of Map3k20 mutations, including split-foot malformation with mesoaxial polydactyly, which is related to hearing loss and exhibits a possible clinical phenotype of cutaneous syndactyly. 26,27 Herein, cutaneous syndactyly was an important malformation in the examined fetus. However, according to mouse experiments and reported pedigrees, the heterozygous deletion of Map3k20 did not induce abnormal morphological changes.…”
Section: Clinical Datamentioning
confidence: 99%